2023
DOI: 10.3322/caac.21785
|View full text |Cite
|
Sign up to set email alerts
|

Clinical insights into small cell lung cancer: Tumor heterogeneity, diagnosis, therapy, and future directions

Abstract: Small cell lung cancer (SCLC) is characterized by rapid growth and high metastatic capacity. It has strong epidemiologic and biologic links to tobacco carcinogens. Although the majority of SCLCs exhibit neuroendocrine features, an important subset of tumors lacks these properties. Genomic profiling of SCLC reveals genetic instability, almost universal inactivation of the tumor suppressor genes TP53 and RB1, and a high mutation burden. Because of early metastasis, only a small fraction of patients are amenable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(44 citation statements)
references
References 387 publications
(839 reference statements)
0
44
0
Order By: Relevance
“…The evidence within the context of pulmonary oncology appears to exhibit a degree of contradiction, which may suggest a dependency on the speci c subtype of lung carcinoma. The speci city of lung cancer subtypes may in uence the pathobiological characteristics and clinical manifestations of the disease, resulting in a heterogeneous response to uniform therapeutic strategies across different subtypes [51]. Here, we found global m 6 A methylation level was increased, while ALKBH5 was downregulated in radon-exposed lung cells.…”
Section: Discussionmentioning
confidence: 63%
“…The evidence within the context of pulmonary oncology appears to exhibit a degree of contradiction, which may suggest a dependency on the speci c subtype of lung carcinoma. The speci city of lung cancer subtypes may in uence the pathobiological characteristics and clinical manifestations of the disease, resulting in a heterogeneous response to uniform therapeutic strategies across different subtypes [51]. Here, we found global m 6 A methylation level was increased, while ALKBH5 was downregulated in radon-exposed lung cells.…”
Section: Discussionmentioning
confidence: 63%
“…Yang et al [29] demonstrated increased sensitivity of triple-negative breast cancer to PD-1 immunotherapy by restoring the activity of p53 protein carrying TP53 mutations. Megyesfalvi Z et al [30] found widespread inactivation of the TP53 gene in small cell lung cancer, suggesting potential e cacy of immunotherapy in this context. Chen et al [31] reported the rst case of CAR-T cell therapy in an LFS patient with hematological malignancy, suggesting that CAR-T cell therapy may be an alternative option compared to traditional chemotherapy and allogeneic hematopoietic stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…As well as this dilemma is avoided by completing a whole immunochemistry panel. The most needed in practice are neuroendocrine markers, such as chromogranin, synaptophysin, and CD56; another new neuroendocrine marker is INSM1 [11].…”
Section: Discussionmentioning
confidence: 99%